Quality of sleep among university students: effects of nighttime computer and television use Qualidade do sono entre universitários: os efeitos da utilização do computador e televisão no período da noite - Gema Mesquita; Rubens Reimão (Arquivos de Neuro-Psiquiatria, 2010)
This descriptive, cross-sectional study was based on subjective questionnaires that assessed nighttime habits of television viewing and Internet use during weekdays and perceived sleep quality among university students. Sleep perception was measured using the Pittsburgh Sleep Quality Index (PSQI). The study group comprised 710 university students aged 17-25 years. Analysis of sleep perception in relation to internet use revealed that 58.06% of subjects who accessed the internet between 19:00 and 21:00 slept poorly; 71.43% between 19:00 and 22:00; 73.33% between 19:00 and 24:00; and 52.38% between 19:00 and 03:00 (p=0.0251). Concerning the relationship between television exposure and perceived sleep, the groups did not differ from each other (p=0.9303). This study showed that internet use between 19:00 and 24:00 increases the risk of poor sleep among young adults, in comparison with television viewing times. Este estudo transversal descritivo com base em questionários subjetivos avalia o hábito de assistir TV e acessar a internet durante as noites nos dias de semana e a percepção da qualidade do sono entre universitários. Para avaliar a percepção do sono foi aplicado o Índice de Qualidade do Sono de Pittsburgh. O grupo estudado incluiu 710 universitários entre 17-25 anos. Para as análises da percepção do sono relacionado ao hábito de acessar o computador observou-se que acessam a internet e dormem mal: 58,06% entre as 19 e as 21h; 71,43% entre as 19 e as 22h; 73,33% entre as 19 e as 24h; 52,38% entre as 19 e as 3h (p=0,0251). Em relação aos horários de assistir TV e a percepção do sono os grupos não se diferenciaram entre si (p=0,9303). O estudo demonstra que acessar a internet durante os horários das 19 às 24h aumenta as chances dos jovens dormirem mal quando comparado aos horários de assistir TV.